PERANCANGAN APLIKASI BERBASIS WEB MENGGUNAKAN SDLC UNTUK PENGEMBANGAN SEKTOR PARIWISATA DAN UMKM - Azman Ba’da; Taufik Ismail Simanjuntak; Puji Chairu Sabila (Jurnal Widya, 2025)
In the modern era, information system technology is well designed and created to increase efficiency, reduce unnecessary things, improve service quality, coordinate every part in a company and organization in order to achieve improved management quality. One of the significant technological developments is the use of the Internet. In the context of tourism, the use of information technology can provide significant benefits. Central Tapanuli Regency has rich tourism potential and a rapidly growing MSME sector, but still needs improvement in the utilization of information technology. This research aims to design and develop web-based applications that utilize the SDLC (Software Development Life Cycle) Method to increase the potential of the tourism sector and MSMEs in Central Tapanuli Regency. The SDLC method is used as a systematic approach in application development to nsure that the resulting application is in accordance with user and environmental needs. This research includes the stages of needs analysis, system design, application implementation, testing, and maintenance.The results of this research are expected to make a significant contribution in improving the accessibility of tourism information as well as the operational efficiency of MSMEs in Central Tapanuli Regency through the use of well-integrated web-based applications. Keywords: information system, tourism, Software Development Life Cycle